RESTORATION OF THE DIELECTRIC PERMITTIVITY PROFILE OF LAYERED STRUCTURES USING THE GELFAND-LEVITAN-MARCHENKO METHOD - Aleksin, S.; Lebedev, S.; Drobakhin, O.O. (Radio Electronics, Computer Science, Control, 2024)
Considered are applied problems related to the usage of Gelfand – Levitan – Marchenko’s method as acceleration iterrational procedure, methods to obtain impulse characteristics, consideration of non-flat character of probing wave, influence of energy losses in a sample as to the result of the building-up of the profile.